THE EFFECT OF WORK DISCIPLINE, INCENTIVES, WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE MEDIATED BY JOB SATISFACTION IN OIL AND GAS COMPANIES IN BATAM CITY - Riana, Sheril Fitri; Dhita Hafizha Asri (Program Sarjana Manajemen Universitas Internasional Batam, 2024)
Employee performance can be influenced by various factors, including work discipline, incentives, and work environment. When these factors are good or good, they can lead to increased employee performance. This research aims to examine the influence of work discipline, incentives and work environment on employee performance at oil and gas companies in Batam City, with job satisfaction as a mediating factor. The research methodology uses Structural Equation Modeling (SEM) analysis using SmartPLS. This research involved 431 employee respondents and the results showed that work discipline, providing incentives and the work environment had a significant and positive effect on job satisfaction. Furthermore, job satisfaction has a significant effect on employee performance, and the combined impact of work discipline, incentives, and work environment on employee performance has a significant positive value which is mediated by job satisfaction.